2014
DOI: 10.1039/c4ra03896g
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional particle coating by plasma process and its application to pollution control

Abstract: Multifunctional particle coating by Plasma-Enhanced Chemical Vapor Deposition (PECVD) and its application are presented in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…2h ) with non-appreciable pores. In previous publications, we have demonstrated that these experimental conditions lead to the formation of microporous thin films with a relative high volume of pores 38 . On the other hand, Fig.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…2h ) with non-appreciable pores. In previous publications, we have demonstrated that these experimental conditions lead to the formation of microporous thin films with a relative high volume of pores 38 . On the other hand, Fig.…”
Section: Resultsmentioning
confidence: 81%
“…This methodology is straightforwardly applicable to other oxides deposited by PECVD like SiO 2 , SiO x C y H z , Al 2 O 3 , Ta 2 O 5 , oxynitrides, doped oxides, etc. and even to metal (Au, Ag) layers deposited by magnetron and DC-sputtering 35 36 37 38 39 40 . As example, Video 2 in the SI shows a 3D HAADF-STEM reconstruction of an Ag-NPs@ZnO@nano-TiO 2 nanotube where silver nanoparticles (NPs) were deposited by DC sputtering in a previous step to the formation of the ZnO shell.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations